Federalismo fiscal no Brasil a partir da LRF: a Lei de Responsabilidade Fiscal e seus impactos no aumento ou diminuição das variáveis observadas nas finanças dos municípios brasileiros - Silva, Ângelo Alves da (2017)
The impacts of the Brazilian Fiscal Accountability Law (FAL) are analyzed with regard to variables´ increase or decrease in the public accounts of Brazilian municipalities, particularly on the expenditure item INVESTMENTS and on government administration in EDUCATION and HEALTH, between 2001 and 2005 (after FAL) compared to the 1996-2000 period (prior to FAL). Current research was foregrounded on the expectation that FAL may have contributed to leverage resources applied in the expenditure item and on several governmental functions, with special reference to Education and Health, the aim of current investigation. This is due to the fact that FAL has restricted expenditure on personnel and limited the debt capacity of Brazilian municipalities. Results reveal that, within the context of 2,644 big or small municipalities under analysis throughout the country, FAL´s impacts failed to cause a behavioral homogeneity with regard to budget growth or decrease. In other words, after the promulgation of FAL, several municipalities significantly increased their public Investments on Education and Health administration functions; others increased moderately or timidly their expenditures; others still, significantly, moderately or timidly decreased their expenditures. There was no uniform pattern for the achievement of the above budget items. The above data reveal the heterogeneity of the municipalities´ accounts, or rather, some had a healthy equilibrium, while others were in great debts prior to FAL. Whereas FAL´s impact on the former municipalities were positive due to increase in Investments and in expenditure on Education and Health, in the later, the new administrations feared the impacts of accountability of their activities, stepped on the brakes, decreased Investments and expenditure in Education and Health to maintain an equilibrium in public accounts.